Interstitial adenosine concentration during norepinephrine infusion in isolated guinea pig hearts - GORMAN, MARK W. (1991)
This study determined the effect of norepinephrine (NE) on cardiac interstitial fluid adenosine concentration ([ADO](isf)). Isolated guinea pig hearts were perfused with a Krebs-Henseleit buffer solution. Radiolabeled albumin, sucrose, and adenosine were injected under control conditions and after 3 and 20 min of NE infusion to obtain multiple indicator dilution curves that were used to determine capillary transport parameters for adenosine. These parameters together with venous adenosine concentrations were used in a mathematical model to calculate [ADO](isf). Capillary transport parameters were not changed significantly by NE infusion. Because of uncertainty regarding two model parameters, two sets of [ADO](isf) values were calculated. One set used best-fit values obtained from indicator dilution curves, and a second set used parameters chosen to provide the highest [ADO](isf) values consistent with indicator dilution curves. Venous adenosine concentrations were 1.9 ± 0.4 nM under control conditions and 243 ± 110 and 45 ± 25 nM after 3 and 20 min of NE infusion, respectively. Calculated [ADO](isf) was 2.6–9.4, 591–1,288, and 166–324 nM, respectively, under these same conditions. We conclude that NE infusion greatly increases [ADO](isf), and adenosine is responsible for most of the vasodilation at 3 min. The subsequent fall in venous concentration is due to a fall in [ADO](isf) rather than to decreased capillary permeability. Vascular resistance remained low while [ADO](isf) fell, which suggests that additional vasodilators are important during maintained NE infusion.